Economic Impacts of Natural Disasters in Brazilian Municipalities and the Focus of the BNDES PER Program - Agostini Martini, Ricardo; Campello Gallo, Maria Eduarda (Revista Economia Ensaios, 2024)
The aim of this study is to evaluate the targeting of the BNDES Emergency Program for the Reconstruction of Municipalities Affected by Natural Disasters (BNDES PER) in Brazilian municipalities. The impact of natural disasters on economic activity in the municipalities was estimated using the synthetic control methodology. The program’s targeting was estimated using logistic regression and fixed effects methods, taking the estimated impact as the regressor. Looking at data from 2008 to 2017, it was found that natural disasters had a negative impact on the GDP per capita of most of the affected municipalities, with effects lasting up to three years after the events. On the other hand, the BNDES PER was able to reach the most intensely impacted municipalities in terms of GDP per capita and value added by services per capita.